Oil and source correlation and its geological significance of Fengcheng 1 well block in Wuxia fault zone, Junggar Basin - Guanbo LIU; Shijia CHEN; Wenjun HE; Yangyang ZHANG (Shiyou shiyan dizhi)
As the conventional oil and gas exploration in the Wuxia fault zone of the western uplift of the Junggar Basin enters its later stages, great breakthroughs have been made in shale oil exploration of the Lower Permian Fengcheng Formation in the past two years. In the process of exploring the accumulation patterns of conventional and shale oil reservoirs in the Fengcheng Formation, it was found that previous understanding of the oil sources in Fengcheng 1 well block was inaccurate. Earlier researchers believed that crude oil in this well block was solely derived from the source rocks of the Fengcheng Formation. To reevaluate this understanding, various organic geochemical data from Permian source rocks and crude oil in existing exploration wells of this area were systematically analyzed. By applying the geochemical oil and source correlation theory and petroleum geology theory, and using chromatography, chromatography-mass spectrometry, and carbon isotope data from source rocks and crude oil, the study reexamined the oil sources in various oil-producing formations in the well block, combined with single-well simulations of source rock thermal evolution history. The results showed that the lower gray-black and black mudstone section of the Lower Permian Jiamuhe Formation, with a thickness of approximately 95 m, had a sedimentary environment and parent material type similar to those of the Fengcheng Formation. However, the parent material type in the Jiamuhe Formation was relatively more humic, with higher organic matter abundance, making it a highly mature humic type, good to high-quality source rocks. The mature crude oil in the upper part of the first member of the Fengcheng Formation in Fengcheng 1 well originated from the source rocks of the Fengcheng Formation. The highly mature crude oil in the two lower oil layers and the Jiamuhe Formation oil layer in Fengcheng 011 well mainly sourced from the source rocks of the Jiamuhe Formation, with a small contribution from the source rocks of the Fengcheng Formation, rather than exclusively from the source rocks of the Fengcheng Formation. It is speculated that the source rocks of the Jiamuhe Formation have a wide spatial distribution range and can provide substantial oil and gas resources for conventional oil and gas accumulation in the Wuxia fault zone. Therefore, it is recommended to strengthen the research on the thickness distribution of source rocks of the Jiamuhe Formation in this area, providing a basis for identifying new oil and gas exploration fields.